TAMBANG EMAS ILEGAL DAN KERUSAKAN SOSIAL-EKOLOGIS DI KABUPATEN BUNGO: STUDI KRITIS ATAS PRAKTIK PETI DAN PERAN PEMERINTAH LOKAL - Putra, Didik Try; Mardansyah, Mardansyah; Epriadi, Dedi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Unauthorized gold mining (PETI) in Bungo Regency causes significant social and ecological impacts, including environmental damage and social tensions between communities and authorities. This research aims to analyze PETI practices and evaluate the local government's role in handling illegal gold mining. The method used is a critical study with data collection from enforcement operation documents and related reports. Research results show that although the government conducts intensive enforcement operations, communities' economic dependence on PETI remains the primary sustainability challenge. The government strives to regulate community mining to make it legal and environmentally friendly through spatial planning policies and community education. In conclusion, a collaborative approach is needed that considers legal, social, and environmental aspects for sustainable solutions that maintain balance between law enforcement, environmental preservation, and community welfare. Keywords: Illegal Gold Mining; PETI; Environmental Damage; Social Impacts; Local Government